Interventions to enhance mental health outcomes of persons with schizophrenia during the COVID-19 pandemic: A systematic review - Sudaporn Stithyudhakarn; Penpaktr Uthis; Trieu Van Nhat (Nursing Practice Today, 2025)
Background & Aim: Schizophrenia is a chronic mental disorder requiring continuous care. During the COVID-19 pandemic, people with schizophrenia (PLWS) faced disproportionate challenges due to healthcare disruptions. Ensuring continuity of care is essential, and understanding the types of interventions implemented during this period can inform future support strategies. This systematic review aimed to identify, describe, and synthesize reported outcomes of interventions implemented to support the mental health of PLWS during the COVID-19 pandemic. Methods & Materials: The protocol was registered on PROSPERO. A comprehensive search was conducted in MEDLINE, Embase, CINAHL, and ScienceDirect for studies published between 2019 and 2023. Eligible studies included experimental (randomized controlled trials and quasi-experimental studies) and non-experimental (observational) designs investigating the effects of interventions on mental health outcomes in PLWS aged 18 years and older. A narrative synthesis was used to report findings, and the quality of included studies was assessed. Results: Of the 1,738 records screened, eleven studies met the inclusion criteria, comprising seven experimental and four non-experimental studies. Interventions included virtual and in-person guided walking, smartphone apps, animated audio-visual videos, animal-assisted therapy, nutritional programs, and incentivized community health worker models. Non-experimental studies reported on telehealth-delivered psychotherapies, vitamin D supplementation, and dietary interventions. These interventions were associated with reported improvements in physical activity, cognitive and social functioning, quality of life, and health behaviors, along with reductions in illness severity, self-stigma, and metabolic risk. Conclusion: This review highlights a range of interventions reported to support the mental health of PLWS during the COVID-19 pandemic. While experimental studies suggest promising outcomes, findings from non-experimental designs require cautious interpretation. These insights may inform the development of flexible, evidence-informed strategies for PLWS in future public health crises.